Opór wobec procesów w sprawie zbrodni wojennych: masakra w Malmédy, niemieckie Kościoły a kontrwywiad amerykański CIC - Jerome S. Legge, Jr. (Zagłada Żydów)
War crimes trials roused considerable resistance in Germany. Here the author analyzes opposition to the Malmédy Trial, conducted at Dachau in 1946, citing documents made available under the 1998 Nazi War Crimes Disclosure Act – in particular those of Roman Catholic auxiliary bishop of Munich Johannes Neuhäusler and regional Protestant bishop Theophil Wurm of Württemberg. These clergymen helped reduce sentences and obtain clemency for perpetrators. Munich lawyer and activist Rudolf Aschenauer, a close associate of Neuhäusler, coordinated a large network devoted to thwarting the convictions of the former Waffen-SS men. The author traces U.S. Army Counterintelligence Corps (CIC) monitoring of both Aschenauer and the bishops.